A new approach to the spectrophotometric determination of metronidazole and tinidazole using p-dimethylaminobenzaldehyde - Adegoke, Olajire Aremu (Array, 2009)
U radu je opisan novi način spektrofotometrijskog određivanja metronidazola (MZ) i tinidazola (TZ)